Drinking Motives Mediate the Relation between Attention-Deficit/Hyperactivity Disorder Symptoms and Alcohol-Related Problems among College Students. Issue 3 (June 2023) - Falco, Caitlin A.; Zimmerman, Lauren; Vasko, John M.; Meinzer, Michael C.; Hartung, Cynthia M.; Flory, Kate; Looby, Alison
Evidence demonstrates an association between symptoms of attention-deficit/hyperactivity disorder (ADHD) and alcohol outcomes, though mechanisms underlying relations are unclear. Given that drinking motives (coping-anxiety, coping-depression, enhancement, social, and conformity) appear to serve as a mediator through which other factors influence drinking behavior, the current multi-site study examined the relation between ADHD symptoms and alcohol outcomes through motives. Past-month drinkers completed online measures assessing ADHD symptoms, alcohol use and problems, and drinking motives. A multiple-mediator model found inattention symptoms were: 1) positively associated with coping-depression, which positively related to alcohol use, which positively related to alcohol problems; 2) positively associated with enhancement motives, which positively related to use, which positively related to problems; and 3) positively associated with coping-anxiety, which negatively related to use, which positively related to problems. No indirect relations via motives were found for hyperactive-impulsive symptoms. Findings highlight unique associations depending on ADHD symptoms and specific drinking motives.